Comparative Study of Bearing Loads for Open Ended Pipe and H-Piles in Sandy Soil - M.A.M. Al-Neami; M.H. Wasmi (Engineering and Technology Journal, 2017)
This paper clarifies the response of steel piles installed in sand under vertical static compression load. To evaluate the ultimate load capacity of both piles, the results were introduced in a comparison form. Pile capacity of open ends pipe pile is affected by degree of soil plugging and sometimes the removal of soil plug may decrease the friction between soil and inner shaft of pile and causes a reduction in the load capacity. Therefore, to avoid plugging phenomenon occurred during piles installation; H-piles sections are manufactured based on the equivalent area steel of open pipe piles and tested under the same conditions. 36 steel piles with lengths equal to (30, 40, and 50) cm are tested. The piles are embedded using jacking technique in sandy samples with two different relative densities; medium sand (60%) and dense sand (80%).The results showed that H-pile has a load capacity greater than open ended pipe pile and increases with the increase in both length and diameter (width of flange) of pile. When relative density increased, plugging phenomenon does not occur in H-pile therefore, it can be used instead of open-ended pipe pile to get rid of plugging phenomenon problems.